TRUST CENTRIC FRAMEWORK FOR ARTIFICIAL INTELLIGENCE INTEGRATION IN PUBLIC ADMINISTRATION - Shaza Khalid (Budi Luhur Journal of Strategic & Global Studies, 2026)
Abstract: Artificial Intelligence (AI) and digital transformation are changing the global public governance landscape in today's fast-changing world. This paper addresses the important nexus of technological progress and institutional trust in the context of the Presidential Decree, which has been proclaimed as the Year of Digitalization and Artificial Intelligence. While AI can introduce an unprecedented level of efficiency and data-driven decision-making in public administration, it is also associated with the "black box" issue, where algorithmic processes raise citizen skepticism and resistance within public administration. This study adopts a qualitative and conceptual approach, aiming to address the question: How can public institutions build and maintain trust during the application of AI? Based on the concepts of Trust Management and Knowledge Management, the study posits a "Trust-Centric Framework" for digital government. The four pillars of this framework are Transparency, Accountability, Competence and Benevolence. To ensure the sustainable digital transformation of the civil service in Kazakhstan, it is necessary to focus not only on technical infrastructure but also on socio-technical management of trust. The study concludes that the implementation of AI is not merely a technological change but a fundamental transformation of the organization, which must be accompanied by new digital skills for civil servants and extensive ethical-legal frameworks. This study brings together international good practice and the geopolitical situation in Kazakhstan to provide policy recommendations for administrators. Abstrak: Kecerdasan Buatan (AI) dan transformasi digital sedang mengubah lanskap pemerintahan publik global di dunia yang cepat berubah saat ini. Penelitian ini membahas hubungan penting antara kemajuan teknologi dan kepercayaan institusional dalam konteks Keputusan Presiden, yang telah diumumkan sebagai Tahun Digitalisasi dan Kecerdasan Buatan. Sementara AI dapat memperkenalkan tingkat efisiensi yang belum pernah terjadi sebelumnya dan pengambilan keputusan berbasis data dalam administrasi publik, AI juga terkait dengan masalah "kotak hitam", di mana proses algoritmik menimbulkan skeptisisme dan resistensi warga dalam administrasi publik. Studi ini mengadopsi pendekatan kualitatif dan konseptual, dengan tujuan untuk menjawab pertanyaan: Bagaimana institusi publik dapat membangun dan mempertahankan kepercayaan selama penerapan AI? Berdasarkan konsep Manajemen Kepercayaan dan Manajemen Pengetahuan, studi ini mengusulkan "Kerangka Berbasis Kepercayaan" untuk pemerintahan digital. Empat pilar dari kerangka ini adalah Transparansi, Akuntabilitas, Kompetensi, dan Kebajikan. Untuk memastikan transformasi digital yang berkelanjutan dari layanan sipil di Kazakhstan, perlu untuk fokus tidak hanya pada infrastruktur teknis tetapi juga pada manajemen sosial-teknis kepercayaan. Studi ini menyimpulkan bahwa penerapan AI bukan sekadar perubahan teknologi tetapi transformasi mendasar dari organisasi, yang harus disertai dengan keterampilan digital baru bagi pegawai negeri dan kerangka etika-hukum yang luas. Studi ini menggabungkan praktik baik internasional dan situasi geopolitik di Kazakhstan untuk memberikan rekomendasi kebijakan bagi para administrator.